PENGARUH PROFITABILITAS TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Dwiyani Hadiwidjaja, Rini; Fera Triani, Lely (LPPM Universitas Terbuka, 2009)
Manufacture industries decline in 2006 was caused by 3 big obstructions, its instability in macroeconomics, uncertainty policy and corruptions. This condition caused the payment of dividend manufactures companies decline year to year and some companies didnt paid the dividend for 3 years respectively. The objective of this research is to find out and analyzes the influence of Cash Ratio, Net Profit Margin (NPM), dan Return on Investment (ROI)) to dividend payout ratio at manufactured industry in Indonesia and which factor will be the most dominant to Dividend Payout Ratio (DPR). The data used in this research is from the yearly financial report of the thirty one manufactured industries listed at the Indonesia Stock Exchange (IDX) at 2001 to 2006. The types of research are descriptive and quantitative with the explanatory research method. The analysis of method used in this research is the multiple linear regressions method. The hypothesize test used the statistical of F-test and the statistical of t-test with confident interval 95% and level of significant 5%. The statistical of F-test shows that all independent variables simultaneously influence DPR at the determinant coefficient (R2) 62,1% its shows that research independent variables able to explain 37,9% to DPR while the remaining of 56,7% explained by independent variables that were un-research. The statistical of t-test shows that only ROI partially influence DPR. Return on Investment is the most variable that influence DPR